2012
DOI: 10.4102/sajim.v14i1.507
|View full text |Cite
|
Sign up to set email alerts
|

Analysing lawyers’ attitude towards knowledge sharing

Abstract: Objectives: The study examined and identified the factors that affect lawyers’ attitudes to knowledge sharing, and their knowledge sharing behaviour. Specifically, it investigated the relationship between the salient beliefs affecting the knowledge sharing attitude of lawyers’, and applied a modified version of the Theory of Reasoned Action (TRA) in the knowledge sharing context, to predict how these factors affect their knowledge sharing behaviour.Method: A field survey of 273 lawyers was carried out, using q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
2
13
0
2
Order By: Relevance
“…Wu and Zhu (2012) defined KS as a degree to which knowledge workers share their knowledge with their colleagues or peer groups. KS is the act of making the required knowledge accessible to others within organizations (Olatokun and Elueze, 2012). KS is the key element for transforming personal knowledge into organizational knowledge (Nonaka, 1994;Foss et al, 2010).…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Wu and Zhu (2012) defined KS as a degree to which knowledge workers share their knowledge with their colleagues or peer groups. KS is the act of making the required knowledge accessible to others within organizations (Olatokun and Elueze, 2012). KS is the key element for transforming personal knowledge into organizational knowledge (Nonaka, 1994;Foss et al, 2010).…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…The findings indicated that social networking tools were effective and that the IBM management team encourages employees to make more use of the tools for knowledge sharing and knowledge creation. Olatokun and Elueze (2013) conducted a field survey in Ibadan, Nigeria to examine the factors that affect lawyers' attitudes to knowledge sharing, and their knowledge sharing behaviour. The study revealed that the level of IT usage significantly affected the knowledge sharing behaviour of lawyers.…”
Section: Strategies For Enhancing Knowledge Retention In Public Sector Organizationsmentioning
confidence: 99%
“…From an organizational behaviour perspective, attitude influence people's behaviour and influence how they interact with other organizational members. A study by Olatokun and Elueze (2012) reveal that attitude towards KS significantly determined the intention to share knowledge, which then determines KS behaviour. Therefore, it is expected that the higher the level of favourable attitude towards KS, the higher the level of interpersonal KS in organizations.…”
Section: Attitudementioning
confidence: 99%